Bidirectional Behavioral Selection in Mice: A Novel Pre-clinical Approach to Examining Compulsivity - Mitra, Swarup; Bult-Ito, Abel (Frontiers in Psychiatry, 2021)
Obsessive-compulsive disorder (OCD) and related disorders (OCRD) is one of the most prevalent neuropsychiatric disorders with no definitive etiology. The pathophysiological attributes of OCD are driven by a multitude of factors that involve polygenic mechanisms, gender, neurochemistry, physiological status, environmental exposures and complex interactions among these factors. Such complex intertwining of contributing factors imparts clinical heterogeneity to the disorder making it challenging for therapeutic intervention. Mouse strains selected for excessive levels of nest- building behavior exhibit a spontaneous, stable and predictable compulsive-like behavioral phenotype. These compulsive-like mice exhibit heterogeneity in expression of compulsive-like and other adjunct behaviors that might serve as a valuable animal equivalent for examining the interactions of genetics, sex and environmental factors in influencing the pathophysiology of OCD. The current review summarizes the existing findings on the compulsive-like mice that bolster their face, construct and predictive validity for studying various dimensions of compulsive and associated behaviors often reported in clinical OCD and OCRD.